2024
DOI: 10.1109/ojies.2024.3366082
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Synchronous Machine Control for Doubly Fed Induction Machine-Based Wind Energy Conversion Systems

ANDRE THOMMESSEN,
Christoph Michael Hackl

Abstract: Renewable inverter-based resources (IBRs), such as wind energy conversion systems (WSs), replace directly grid-connected synchronous machines (SMs). Standard grid-following (GFL) control of IBRs decreases the power system inertia. This paper proposes virtual synchronous machine (VSM) based gridforming (GFM) control for doubly-fed induction machine (DFIM) based wind energy conversion systems (WSs) with the following extensions: (i) feedforward torque control (FTC) for maximum power point tracking (MPPT), (ii) M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…As demand increases, additional conventional power deployment units are being built in different places [3,4]. However, these fossil fuel-based conventional power generation plants are producing harmful chemicals, such as carbon dioxide, nitrogen monoxide, carbon monoxide, sulphur dioxide, and other toxic pollutants in the open environment, which is catastrophically breaking the ozone layer of the environment, in turn contributing to high global warming every year [5,6]. Previous research studies have shown that the amount of carbon dioxide released into the atmosphere yearly from traditional power plants is 2.2 billion tons, which needs to Energies 2024, 17, 2737 2 of 33 be reduced by around 40%, according to the Paris Agreement, by 2030 [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…As demand increases, additional conventional power deployment units are being built in different places [3,4]. However, these fossil fuel-based conventional power generation plants are producing harmful chemicals, such as carbon dioxide, nitrogen monoxide, carbon monoxide, sulphur dioxide, and other toxic pollutants in the open environment, which is catastrophically breaking the ozone layer of the environment, in turn contributing to high global warming every year [5,6]. Previous research studies have shown that the amount of carbon dioxide released into the atmosphere yearly from traditional power plants is 2.2 billion tons, which needs to Energies 2024, 17, 2737 2 of 33 be reduced by around 40%, according to the Paris Agreement, by 2030 [7,8].…”
Section: Introductionmentioning
confidence: 99%